FREE RADICALS SCAVENGING AND INHIBITION OF LIPID PEROXIDATION BY SALVADORA PERSICA LINN. - MANGAL SAIN HOODA,; JANARDHAN SINGH, (International Journal of Pharma and Bio Sciences, 2012)
Salvadora persica (Salvadoraceae) is widely used in Unani system of medicine. Its root and stem were extracted using solvents of different polarities and explored for in-vitro free radical scavenging activity and lipid per-oxidation assay in rat brain homogenate. Preliminary assays of six different extracts of Salvadora persica, scavenges 1,1-diphenyl-2-picrylhydrazyl stable free radicals in concentration dependent manner. All studied extracts possess electron donating ability and reduce ferric ion to ferrous in a cell free system at pH-7.4. Also, 250 and 500µg/ml alcoholic and hydro alcoholic extracts reduced the activated lipid per-oxidation in rat brain homogenate. Further, both extracts reduced the lipid per-oxidation to the extended time period (1 to 12 hour after initiation of lipid per-oxidation). Root extracts were found more effective when compared to stem in scavenging 1,1-diphenyl-2-picrylhydrazyl, reducing ferric ion and inhibiting the lipid per-oxidation. Hydro-alcoholic extracts were found more effective in scavenging the 1,1-diphenyl-2-picrylhydrazyl and reducing the ferric ions. The significant correlations exist between extract concentrations and percentage scavenging activity of radicals in all models. These results clearly indicate that Salvadora persica is effective free radical scavenger and chain breaking antioxidant.